A Fractal-based Algorithm for the Metamorphic Animation - Chuanbo Chen; Yunping Zheng; Mudar Sarem (2006 International Conference on Information & Communication Technologies : from Theory to Applications : ICTTA '06 : proceedings : 24-28 April 2006, Damascus, Syria, 2006)
The metamorphic technology is one of the most important technologies in the computer animation. This paper presents a new fractal-based algorithm for the metamorphic animation. The conceptual roots of fractals can be traced to the attempts to measure the size of objects for which traditional definitions based on Euclidean geometry or calculus failed. Therefore, the objective of this study is to design a fractal-based algorithm and produce a metamorphic animation based on a fractal idea. The main method we adopted is to weight two IFS (Iterated Function System) codes between the start and the target object by an interpolation function. We test our algorithm on the Matlab software. The experimental results demonstrate that the animation generated according to our method is smooth, natural and fluent. In addition, our algorithm has the merits of stability, efficiency and verisimilitude. This study shows that the fractal idea can be effectively applied in the metamorphic animation. The main feature of our algorithm is that it can deal with a fractal object that the conventional algorithm cannot. In application, our algorithm has many practical values that can improve the efficiency of animation production and simultaneously greatly reduce the cost